La globalización de la Amazonía: una perspectiva andina - Fontaine, Guillaume (2006)
In this paper we present the historical, social, political and economical context in which the Amazon basin is to be considered, from an andean perspective. In the introduction we review a few basic facts about the geografic and demografic state of the region. Then we present the main steps of the human ocupation of the amazon area, from the Conquest to the irruption of capitalism. The second part is dedicated to the internationalization of the amazon agenda, especially throughout the conservation of the environment and the cooperation. We conclude with a short comment on the role of social actors in the region´s future.